Prenatal diagnosis of susceptibility loci for neurodevelopmental disorders – genetic counseling and pregnancy outcome in 57 cases. (29th December 2016) - Govaerts, Lutgarde; Srebniak, Malgorzata; Diderich, Karin; Joosten, Marieke; Riedijk, Sam; Knapen, Maarten; Go, Attie; Papatsonis, Dimitri; de Graaf, Katja; Toolenaar, Toon; van der Steen, Sanne; Huijbregts, Gido; et al.
Abstract: Background: Whole genome array testing not only provides an increased diagnostic yield of pathogenic causative findings, but it may also reveal so called susceptibility loci (SL) for neurodevelopmental disorders. The goal of this study was to evaluate the pregnancy outcomes in SL cases and to establish a protocol for pregnancy management, follow‐up and additional investigations. Methods: Fifty seven cases were evaluated: 34 with and 23 without ultrasound anomalies at referral. Each pregnant couple received pretest counseling and extensive posttest genetic counseling. Results: After diagnosis of SL, parental testing and an additional ultrasound examination were offered. The severity of the ultrasound anomalies and not the diagnosis of SL was the most important factor contributing to the decision on pregnancy continuation. In the majority of cases with milder or no ultrasound anomalies, the pregnancy was continued and a normal outcome after birth was observed. Conclusions: The diagnosis of a SL did not seem to be a reason for termination of pregnancy. Most patients were able to cope with the uncertainty and were interested in both prenatal and postnatal actionability of SL. Long‐term follow‐up is crucial to assess the actual risks for neurodevelopmental disorders, especially in families with unremarkable history. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Genomic array is now recommended in cases of congenital anomalies and stillbirths. So called susceptibility loci (SL) for neurodevelopmental disorders are diagnosed prenatally in about 1–3% of the pregnancies. What does this study add? The severity of the ultrasound anomalies and not the diagnosis of SL for neurodevelopmental disorders was the most important factor contributing to the decision on pregnancy continuation. In a large majority of cases with milder or no ultrasound anomalies, the pregnancy was continued and a normal outcome at birth was observed. Most patients were interested in both prenatal and postnatal actionability of SL. Most patients could cope with uncertainty related to SL.